Persistent symptoms and association with inflammatory cytokine signatures in recovered coronavirus disease 2019 patients - Ong, Sean Wei Xiang (2022)
Background: The complications and sequelae of coronavirus disease 2019 (COVID-19) and their effect on long-term health are unclear, and the trajectory of associated immune dysregulation is poorly understood.